The socio-practical dimensions of isitshisa [ burning of the heifer ] in the Corinthian Church of South Africa - Mbaya, Henry (HTS teologiese studies, 2011)
In this article, I argued that the performances of the ritual sacrifice of burning the heifer [isitshisa] and worship, held annually at Mlazi in Durban by the members of the Corinthian Church of South Africa, has social implications. Not only does the ritual worship enhance religious bonds of affinity amongst the Corinthians, it also instils in them the values of sharing, cooperation and care for those in need in the community, for example the blind; thus, isitshisa acts as a resource that empowers the Corinthians for social commitment and action in their community.